Análisis de deforestación por medio de percepción remota en las cuencas del rio Portoviejo - Chone. - López Álava, Geoconda Aracely (2015)
Deforestation is a worldwide problem in watersheds, caused by human activities since colonization until now, they have produced large deforested areas. The objective of this research was to determine deforestation through remote sensing for the Portoviejo - Chone River basins, for which the geographic information system was used as an analytical tool; remote sensing technique with Landsat and Spot satellite images were available for the study. Changes of the land between 1998 - 2014 show a total deforestation rate of 16,55% in the watersheds for 16 years. The classification of land and analysis of coverage of the basins is performed using the supervised classification determining that vegetative cover of the watershed between 1998 2000 is 332,782 ha, for 2000-2008 is 241 167 ha and from 2008 to 2014 is 331,728 ha. The deforestation rate was found for the period 1998-2000 is 14.8% within 2 years, the area covered by clouds and shadows is a constraint to change the areas, mostly in the area covered by vegetation was also analyzed naturally, this was due to increased coverage for the year 1998-2000, and 2008-2014 as well as decrease for 2000-2008.